To simplify the expression \( (4 - 2x)(-6x^2 + 10x + 21 - 2x) \), we first simplify the second expression inside the parentheses:
\[ -6x^2 + 10x + 21 - 2x = -6x^2 + (10x - 2x) + 21 = -6x^2 + 8x + 21 \]
Now, we rewrite the entire expression:
\[ (4 - 2x)(-6x^2 + 8x + 21) \]
Next, we will use the distributive property (often called the FOIL method for binomials) to multiply these two expressions. We can distribute \( 4 \) and \( -2x \) across the polynomial:
- \( 4 \cdot -6x^2 = -24x^2 \)
- \( 4 \cdot 8x = 32x \)
- \( 4 \cdot 21 = 84 \)
- \( -2x \cdot -6x^2 = 12x^3 \)
- \( -2x \cdot 8x = -16x^2 \)
- \( -2x \cdot 21 = -42x \)
Now we combine all of these results:
\[ 12x^3 + (-24x^2 - 16x^2) + (32x - 42x) + 84 \]
This simplifies to:
\[ 12x^3 - 40x^2 - 10x + 84 \]
Now we can write the expression in standard form:
\[ 12x^3 - 40x^2 - 10x + 84 \]
Thus, our simplified polynomial is:
\[ \boxed{12x^3 - 40x^2 - 10x + 84} \]
This expression can be irreducible in its current form, so we leave it as is.